Predicting the Size and Duration of the COVID-19 Pandemic - Lewis, Ted G.; Al Mannai, Waleed I. (Frontiers in Applied Mathematics and Statistics, 2021)
In this paper we answer the questions how long will Covid-19 last in Bahrain with a finite population of 1.7M, and what is its final size? We compare the predictions made by numerical solutions of variations of the Kermack-McKendrick(KM) SIR Epidemic model and Tsallis-Tirnakli model with the curve fitting solution of the Bass model of product adoption. The results show that estimating parameters is a difficult task, which leads to initial predictions far from reality. The Tsallis-Tirnakli and Bass models yield more realistic results using data-driven approaches but greatly differ in their predictions. Finally, we identify possible sources of inaccuracies in predicting COVID-19 duration and size in Bahrain, the United States, and the world. We conclude that additional factors such as variations in social network structure, public health policy, and population are major causes of inaccuracies in estimating size and duration.